2019
DOI: 10.5114/kitp.2019.86359
|View full text |Cite
|
Sign up to set email alerts
|

Early results of optimal septal myectomy using 3-dimensional printed models

Abstract: Introduction The completeness of septal myectomy (SM) is the key to surgery of hypertrophic obstructive cardiomyopathy (HOCM), but its planning is still based on echocardiographic findings. The need to perform radical SM requires the development of new cardio-visualisation techniques for monitoring myectomy quality. Aim To improve results in centres treating few patients with HOCM using a new method of optimal SM with the help of 3-dimensional models to achieve an ‘idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… 13 Across the largest studies, all investigators concluded that the use of 3DPSPs was positive and enhancing in the clinical management of patients with complex geometric cardiovascular conditions. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Tissue mimicry and poor representation of the cardiac valves were frequently shared concerns, particularly with single-material 3DPSPs. 22
Figure 3 Number of Studies Investigating Three-Dimensional Printed Cardiovascular Phantoms and 3-Year Trend Line
…”
Section: Resultsmentioning
confidence: 99%
“… 13 Across the largest studies, all investigators concluded that the use of 3DPSPs was positive and enhancing in the clinical management of patients with complex geometric cardiovascular conditions. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Tissue mimicry and poor representation of the cardiac valves were frequently shared concerns, particularly with single-material 3DPSPs. 22
Figure 3 Number of Studies Investigating Three-Dimensional Printed Cardiovascular Phantoms and 3-Year Trend Line
…”
Section: Resultsmentioning
confidence: 99%
“…Both models, the native and the virtually treated one with its resected fragment guided the surgeon during the intervention in two cases. Besides these case reports, three prospective studies including more than five subjects systematically investigated 3DPSP before myectomy [38,40,41]. Authors evaluated them as a helpful tool in the planning of the intervention and for intraoperative guiding to achieve optimal septum thickness, whereas comparative studies are lacking.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The interactive PDF is easily portable, an advantage compared to 3-D printed heart models. [32][33][34][35][36][37] Readers can access our initial models through the publication by Oberoi et al 32 "Seeing" the operation A common problem in teaching septal myectomy has been the restricted view of the operative field for the assistant resident surgeon. We address this by using video obtained with a standard rigid endoscope directed to the LVOT or transapically when this approach is used.…”
Section: Teaching Myectomy Techniques-the Problemmentioning
confidence: 99%